Analisis Linguistik Wasathiyyah Dalam Al-Qur’an, Hadis Dan Aqwal Ulama - Friendis Syani Amrulloh; Wahyu Ali Mustofa (Academia Publication, 2021)
Wasathiyyah refers to spontaneous, unequivocal, or oblique reactions to anything. Mathematical centers are difficult to define and define, just as passive neutral behavior. Furthermore, contrary to popular belief, the term wasat has two meanings. To eradicate prejudice against wasathiyyah, there is no need to desire the pinnacle of goodness, which comprises knowledge, worship, and worldliness. In the Qur'an, the word wasat appears five times. There are many things that have food in between these two extremes. Each can be found in Al-Baqarah verses 143 and 238 , Al-Qur'an Al-Maidah 89 , Al-Qur'an Al-Qalam 28 , and Al-Qur'an Al-'Adiyat 4-5in the Qur'an .In these verses, the phrase wasath refers to the meanings of midway, just, and choice. Based on the suggested meaning behind this term from a linguistic standpoint, mufassirins and academics express their judgments concerning the features of wasathiyyah in the above verses.